American alchemy : the California Gold Rush and middle-class culture - Roberts, Brian, 1957- (Cultural studies of the United States., 2000)
California during the gold rush was a place of disputed claims, shoot-outs, gambling halls, and prostitution; a place populated by a rough and rebellious figure; a place that seems utterly unconnected to middle-class culture. This work challenges this stereotypical portrait.